1998
DOI: 10.1093/molehr/4.5.503
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits development of embryos and implantation in mice

Abstract: The objectives of this study were to evaluate the effects of a nitric oxide (NO) donor on embryo development in vitro and on implantation of embryos in vivo in mice. Mouse embryos (2-cell) were incubated in media containing different concentrations of diethylenetriamine/NO (DETA/NO), a nitric oxide donor, and development was monitored daily for 4 days. Specificity of NO effects was assessed by using DETA without NO or 48 h preincubated DETA/NO. In in-vivo studies, mated mice were continuously infused, subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 26 publications
2
46
1
3
Order By: Relevance
“…NO is also important in early embryonic survival. However, excessive NO values from exogenous NO donors were found to be harmful to preimplanting and implanting mouse embryos (Barroso et al, 1998). In our study, the NO productions in the serum, uterus and endometrial cells were also increased significantly by LPS.…”
Section: Discussionsupporting
confidence: 45%
“…NO is also important in early embryonic survival. However, excessive NO values from exogenous NO donors were found to be harmful to preimplanting and implanting mouse embryos (Barroso et al, 1998). In our study, the NO productions in the serum, uterus and endometrial cells were also increased significantly by LPS.…”
Section: Discussionsupporting
confidence: 45%
“…The stage specific defects induced by NO depletion underscores the influence of the tissue micro-environment on NO-mediated actions during vascular development. These differences in susceptibility may be the result of developmental stage specific sensitivity to environmental conditions (Barroso et al, 1998;Sengoku et al, 2001). The observed sensitivity of primitive streak conceptuses to changes in NO concentration is currently unexplained; we speculate that differentiation and migratory events that occur in the splanchnic mesoderm specifically at this stage may be affected, while in late head fold stage embryos these events have been completed.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that high concentrations of NO donor (0.1 and 1 mM DETA/NO) in vivo impaired embryo development while lower concentrations (1 and 10 µM) did not cause developmental abnormalities (Barroso et al, 1998;Sengoku et al, 2001). Therefore, we supplemented low doses of a slow, steady release NO donor (NOC-18) to the culture media and assessed the tolerance of the yolk sac to exogenous NO (20 µM) during vasculogenesis.…”
Section: Exogenous No Treatment Results In Normal Vascular Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although higher concentrations of NO could result in better blood flow in the uterine, based on previous studies conducted on mice, it could also inhibit both embryo development in vitro and implantation in vivo [14], which is why discontinuing sildenafil administration before the date of HCG administration was proposed by Sher et al [12]. It has also been proposed that the GMP pathway might be involved in the NOregulated embryonic development, but not in NO-induced apoptosis which could lead to errors during implantation.…”
Section: Discussionmentioning
confidence: 99%